The Real Effects of Financial Sector Risk - Maechler, Andrea (IMF Working Papers; Working Paper, 2009)
This paper estimates the magnitude of key effects on the real economy from financial sector stress. We focus on the short-run feedback effect from market-based indicators of financial sector risk to the real economy through the credit channel, and estimate this effect on an economy-wide (macro) level, as well as on the level of individual large banks. Both estimates yield significant feedback effects of substantial magnitude. The estimates are consistent with other work in this area. Our results suggest that prudential supervision could be enhanced by taking into account the feedback effects of financial instability in the real economy. We also propose a way to integrate feedback effects into stress tests in order to improve realism and accuracy or macroeconomic stress scenarios, as well as a metric to interpret stress testing results.